2013
DOI: 10.1002/ejic.201301250
|View full text |Cite
|
Sign up to set email alerts
|

Coprecipitation of Oxalates: An Easy and Reproducible Wet‐Chemistry Synthesis Route for Transition‐Metal Ferrites

Abstract: In this work, an easy, quick and reproducible wet-synthesis coprecipitation route starting from oxalate precursors was optimised to synthesise cobalt, nickel, zinc and magnesium spinel ferrites CoFe2O4, NiFe2O4, ZnFe2O4 and MgFe2O4, as well as the manganese perovskite ferrite MnFeO3. Crystalline purity and crystallite sizes ranging from 30 to 190 nm were investigated by means of powder X-ray diffraction, and uniform morphology of the particles was shown through transmission electron microscopy. The chosen synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 137 publications
0
26
0
Order By: Relevance
“…The peaks of Mn 2p in Table 2 obviously broadened after the photocatalytic reaction, and the signal at 654.29 eV appeared as a new peak, thereby clearly proving the presence of Mn 3+ [45,46]. The further studies showed, after photocatalytic reaction finished, the XPS spectrum of Mn 2p was deconvoluted into 6 peaks (Fig.…”
Section: Catalytic Mechanism Of Rg-mnfe 2 Omentioning
confidence: 87%
“…The peaks of Mn 2p in Table 2 obviously broadened after the photocatalytic reaction, and the signal at 654.29 eV appeared as a new peak, thereby clearly proving the presence of Mn 3+ [45,46]. The further studies showed, after photocatalytic reaction finished, the XPS spectrum of Mn 2p was deconvoluted into 6 peaks (Fig.…”
Section: Catalytic Mechanism Of Rg-mnfe 2 Omentioning
confidence: 87%
“…by a wet-synthesis coprecipitation route starting from iron(III) nitrate, cobalt(II) chloride and oxalic acid in order to prepare the oxalate precursors. The precipitate was centrifuged, dried and calcined at 873 or 1173 K for 5 h in air [30]. Many researchers used the redox method to synthesize the carboxylate precursors (oxalate, malonate, succinate, etc.)…”
Section: Mixed Metal-oxide Nanoparticles From Carboxylate Precursorsmentioning
confidence: 99%
“…According to XPS and Mössbauer results, the as-synthesized compounds contained surface iron in oxidation state (III) and not in (II). The TPR result showed that the reduction process took place at 700-1173 K and resulted in the reduction of Co(II) and Fe(III) cations to a metallic state [30]. In addition, some researchers have studied the synthesis of [34], with the use of longer chain precursors [31] and the increase of the annealing temperature [36].…”
Section: Structure and Characterization Of Metallic Co Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with the above-mentioned technological applications, these metal oxalates are also important precursors for the synthesis of micro-or nanostructured metal oxides such as manganese oxide, [20] iron oxide, [21] cobalt oxide, [22] nickel oxide, [23,24] copper oxide, [25] zinc oxide, [26] zirconium oxide, [27] and thorium(IV) oxide. [28,29] [30] Thorium(IV) oxalate is an important component for the nuclear industry as it is used in the synthesis of thorium(IV) oxide, which is a fertile material and is used as a blanket material in nuclear reactors. Thorium(IV) oxalate incorporated into a silica gel matrix is proposed to be a new sorbent for the removal of americium from oxalic acid/nitric acid solutions.…”
Section: Introductionmentioning
confidence: 99%